OPTIMIZATION OF LOCAL ORIGINAL INCOME AT THE BITUNG CITY REGIONAL REVENUE AGENCY - Satrio Farli Tangkudung; Fitri H. Mamonto; Goinpeace H. Tumbel (CV. Radja Publika, 2026)
This study aims to describe and analyze the intensification process and evaluate the monitoring mechanisms implemented by the Bitung City Government in optimizing Regional Original Revenue (PAD). The background to this research is the phenomenon of fluctuations in PAD realization, where the Regional Tax sector showed significant growth while the Regional Retribution sector experienced a drastic decline between 2015 and 2025. Furthermore, the regional financial condition facing a debt burden demands stronger fiscal independence The research method used was a qualitative approach with a post-positivistic paradigm. Data were collected through in-depth interviews with key informants from the Regional Revenue Agency (Bapenda) and the Transportation Agency (Dishub), supplemented by field observations and documentation studies. The research focused on the intensification and oversight of parking fees as a potential target. The results of the study indicate that: (1) The parking levy intensification process is not yet optimal due to the collection system which is still manual (tickets), network constraints on digital tools, and inter-agency coordination (Bapenda and Transportation Agency) which is only carried out once a year; (2) The competence of officers in the field is still limited due to the lack of formal technical training; (3) The monitoring mechanism has not been automatically integrated and still relies on the annual audit stage. This study concludes that digitalization of the collection system and increasing the frequency of data reconciliation are crucial to reduce budget leakage and achieve the expected PAD targets.